STUDI SAHAM TUNGGAL DAN PORTOFOLIO: ANALISIS VALUE AT RISK DENGAN METODE VARIANCE-COVARIANCE (SAHAM INDEKS IDX30) - Veronika Waruwu; Andhi Supriyadi (Media Bina Ilmiah, 2025)
Investors must consider risk when investing. To reduce risk, they can diversify by forming a portfolio. This study aims to analyze the risk value that will be experienced by investors within a period of 1 day at a 95% confidence level. The object of the study includes stocks that are consistently listed in the IDX30 index during the period January 2022 December 2023. The research methodology used is the Markowitz method for optimal portfolio formation, the Variance-Covariance method and Historical Simulation to measure Value at Risk, and backtesting using the Kupiec Test model to measure the validity of the Value at Risk method. According to the research results, the stocks that form the ideal portfolio consist of ASII, BBCA, BBNI, BBRI, BRPT, INCO, INDF, KLBF, PTBA, and UNTR. The portfolio risk value is smaller than the risk value of a single stock. The backtesting results of the Historical Simulation method and the Variance-Covariance method show valid results in measuring the maximum potential loss of a stock portfolio